Multimethodological Approach for the Evaluation of Tropospheric Ozone’s Regional Photochemical Pollution at the WMO/GAW Station of Lamezia Terme, Italy - Francesco D’Amico; Giorgia De Benedetto; Luana Malacaria; Salvatore Sinopoli; Arijit Dutta; Teresa Lo Feudo; Daniel Gullì; Ivano Ammoscato; Mariafrancesca De Pino; Claudia Roberta Calidonna (AppliedChem)
The photochemical production of tropospheric ozone (O3) is very closely linked to seasonal cycles and peaks in solar radiation occurring during warm seasons. In the Mediterranean Basin, which is a hotspot for climate and air mass transport mechanisms, boreal warm seasons cause a notable increase in tropospheric O3, which unlike stratospheric O3 is not beneficial for the environment. At the Lamezia Terme (code: LMT) World Meteorological Organization—Global Atmosphere Watch (WMO/GAW) station located in Calabria, Southern Italy, peaks of tropospheric O3 were observed during boreal summer and spring seasons, and were consequently linked to specific wind patterns compatible with increased photochemical activity in the Tyrrhenian Sea. The finding resulted in the introduction of a correction factor for O3 in the O3/NOx (ozone to nitrogen oxides) ratio “Proximity” methodology for the assessment of air mass aging. However, some of the mechanisms driving O3 patterns and their correlation with other parameters at the LMT site remain unknown, despite the environmental and health hazards posed by tropospheric O3 in the area. In general, the issue of ozone photochemical pollution in the region of Calabria, Italy, is understudied. In this study, the behavior of O3 at the site is assessed with remarkable detail using nine years (2015–2023) of data and correlations with surface temperature and solar radiation. The evaluations demonstrate non-negligible correlations between environmental factors, such as temperature and solar radiation, and O3 concentrations, driven by peculiar patterns in local wind circulation. The northeastern sector of LMT, partly neglected in previous works, yielded higher statistical correlations with O3 than expected. The findings of this study also indicate, for central Calabria, the possibility of heterogeneities in O3 exposure due to local geomorphology and wind patterns. A case study of very high O3 concentrations reported during the 2015 summer season is also reported by analyzing the tendencies observed during the period with additional methodologies and highlighting drivers of photochemical pollution on larger scales, also demonstrating that near-surface concentrations result from specific combinations of multiple factors.